2018
DOI: 10.1177/0020764018763692
|View full text |Cite
|
Sign up to set email alerts
|

Friendship and money: A qualitative study of service users’ experiences of participating in a supported socialisation programme

Abstract: Supported socialisation can increase confidence, social competence and self-agency; buffer against psychiatric stigma; build social capital; and afford opportunities to enhance social integration, inclusion and belonging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…It may therefore be suggested that community-based psychiatry services take their responsibility more serious to develop and offer support interventions through which persons who frequently visit PERs can become more socialised and integrated in society. For example, supported socialisation programmes have shown to increase social integration and inclusion as well as the sense of belonging in persons with mental illness (Sheridan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It may therefore be suggested that community-based psychiatry services take their responsibility more serious to develop and offer support interventions through which persons who frequently visit PERs can become more socialised and integrated in society. For example, supported socialisation programmes have shown to increase social integration and inclusion as well as the sense of belonging in persons with mental illness (Sheridan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the remaining studies were concerned with client engagement in activities (Killaspy et al 2015;Sheridan et al 2018) and psychoeducation based on cognitive behavioral therapy (McMurran et al 2011). Killaspy et al (2015) evaluated a staff-training program designed to increase patients' engagement in activities.…”
Section: Societal Recoverymentioning
confidence: 99%
“…In this cluster-randomized trial, no differences were found between the study groups in engagement in activities. Sheridan et al (2018) studied the effects of a supported socialisation volunteer partner group to stimulate social and leisure activities. In their qualitative thematic analyses of diary data they found indications for positive effects on involvement in normalising life, connectedness, physical health, social capacity and culture engagement.…”
Section: Societal Recoverymentioning
confidence: 99%
“…From the users' point of view, the limited number of components indicates that users participate in a limited number of social circles and therefore have limited social roles (Burt, 2004(Burt, , 2005Dozier et al, 1987;Granovetter, 1973). This is important information for professionals, both in the development of social support programmes (Sheridan et al, 2018) and in relation to the support provided by Assertive Community Treatment teams. The association between centralisation and the severity of psychosocial functioning should also be of interest to professionals, as it points to the importance of developing the central role of a professional, for example, in case management.…”
Section: Limitsmentioning
confidence: 99%